CircRNA: A novel biomarker for forensic age estimation?. Issue 1 (December 2019) - Wang, Junyan; Fu, Guangping; Wang, Qian; Cong, Bin; Li, Shujin
Abstract: Aging is a complex process and is associated with various molecular regulations on DNA or RNA levels. In forensic science, accurate age estimation of an unknown individual can be of extremely important. Recent years, age-related molecular biomarkers have been proposed as indicators of chronological age. There were studies showing that circular RNAs (circRNAs) change significantly during aging. Here, the correlation of circRNAs expression levels and age was investigated by detecting circRNA levels in peripheral whole blood utilizing next-generation RNA sequencing (RNA-seq). We suggest that circRNA can be a novel biomarker for forensic age estimation.